Low Temperature Creep/Relaxation Behaviour of PM Steels under Static Load - Vattur Sundaram, Maheswaran (My University, 2014)
Powder metallurgy (PM) is one of the metal forming techniques to manufacture structural components in high volumes. Almost 70% of the PM steels produced are used in automotive applications. This is due to the inherent advantages of the PM process owing to its low cost and near net shaping capabilities along with the possibility of achieving complex shapes while utilizing almost 95% of the raw material with less energy consumption. Utilizing PM components for high performance applications demands good mechanical properties and high dimensional tolerances. In PM steels such properties are achieved, for example by modifying the composition (alloying elements), utilizing different alloying techniques (prealloying, diffusion bonding and admixing) and application of heat treatments (e.g. hardening/sinterhardening, carburising, tempering, etc.). It has recently been found that under certain conditions, PM steel components lack dimensional stability in applications under high static loads over a sustained period of time at temperatures where creep normally doesn’t occur. In high performance applications, such a small dimensional instability could have an adverse effect on the overall performance of the system. Preliminary tests indicate that the components tend to creep/relax at low temperatures under high loading conditions. This phenomenon is a recent observation in PM steels, whereas, in bearing steels and other metallic materials (i.e. Cu, Ti) such behaviour has been discussed earlier. Hence, the creep/relaxation phenomena at temperatures (T/Tm<0.3, temperature in kelvin) in PM steels under high static loading conditions is investigated for diffusion-alloyed powder grade (Distaloy HP produced by Höganäs AB) material. The experiments were performed on the sinterhardened tensile specimens that were additionally heat treated as follows: (i) without any tempering (untempered); (ii) after subsequent tempering at 200°C and 300°C (tempered); (iii) specimens with subsequent quenching in liquid nitrogen directly after sinterhardening (untempered-deep cooled); (iv) sinterhardened and quenched in liquid nitrogen specimens with subsequent tempering at 200°C and 300°C (deepcooled-tempered). The test specimens are characterised and the properties are analysed and evaluated before and after creep tests by XRD, optical and scanning electron microscopy. The results show that each specimen exhibits a unique characteristic behaviour associated with the test temperature and corresponding tempering conditions. However, untempered specimens exhibited a noticeable amount of plastic strain at 120°C when compared to the tempered (at 200°C) specimens. For the specimens tempered at a higher temperature (at 300°C) there is a negligible amount of plastic strain when testing under similar conditions. Also, the deepcooled-tempered specimens exhibited smaller amount of strain when compared to the only tempered samples. This behaviour of the specimens is attributed to the microstructural stability and stress relieve while tempering at high temperatures reduces the dimensional instability of the above studied PM steel under high static loads over a prolonged time period. A more detailed study for understanding this phenomenon in PM steels is required to further widen their application in automotive industry.
Keywords: Produktion; Metallurgisk produktionsteknik; Annan materialteknik; Production; Metallurgical manufacturing engineering; Other Materials Engineering